STRATEGY FOR ENHANCING MATHEMATICAL SKILLS THROUGH THE SMART CORNER IN EARLY CHILDHOOD EDUCATION - Ailsa Syahda Firjatullah (Journal of Art and Creativity in Early Childhood Education, 2025)
This study aims to describe the use of the